Heterogeneous Catalysis under Continuous Flow Conditions - Gupta, Ashu; Gupta, Radhika; Arora, Gunjan; Yadav, Priya; Sharma, Rakesh K. (Current Organic Chemistry, 2023)
Heterogeneous catalysis using continuous flow processing is one of the most demanding subjects from the viewpoint of manufacturing industrial-scale organic compounds. An amalgamation of the two areas of technology, i.e., heterogeneous catalysis and flow chemistry, has opened new avenues for green synthetic chemistry. These processes are particularly convenient in terms of short diffusion paths and improved mixing due to the sensing of high local concentration of catalytic species on solid catalytic surface when the liquid/ gaseous reagents pass through the column, ultimately resulting in quicker and more efficient reaction with increased reaction rates and higher turnover numbers. It imparts several key benefits over conventional batch systems, such as time and energy-saving methodologies, better productivity, reproducibility, economic viability, waste reduction, and ecofriendly nature. Also, it eradicates the need for any intermediate isolation, separation of catalysts, and use of excess reagents. The present review article focuses on heterogeneous catalysis under continuous flow conditions. Various key reactions, for instance, carbon-carbon bond formation, hydrogenation, condensation, and oxidation, are presented well, along with their recent developments in the manufacturing of active pharmaceutical ingredients and platform chemicals. Asymmetric catalysis has also been discussed with its applications in the synthesis of complex organic molecules. It is anticipated that the review article will proliferate significant interest in modernizing chemical syntheses through continuous flow processes.
Keywords: C-C coupling reactions